Tanggung Jawab dan Perlindungan Hukum bagi Notaris secara Perdata Terhadap Akta yang Dibuatnya - Kunni Afifah (Universitas Islam Indonesia, 2017)
AbstractThis study examines the form of liability and legal protection in civil Notary on the deeds made. This law research is empirical juridical kind. The results of this study indicate that a civil liability of a Notary who committed an unlawful act is the Notary shall account for his actions with civil sanctions in the form of reimbursement or compensation to the injured party on an unlawful act committed by a Notary. But before Notary sanctioned civil then Notary must first be proven that there has been any loss arising out of a tort Notary against the parties, and between the losses and the tort of Notaries are causal relationships, and tort or negligence due to an error that can be accounted to the Notary concerned. While the form of legal protection for Notary on the deeds which made related to civil liability Notary is the Honorary Council of notaries who are independent, in this case the existence of MKN not a sub part of the government who appointed him.Keywords: Notary, responsibility in the civil protection law